Atributos físicos e químicos do solo em diferentes sistemas de manejo em uma propriedade no município de Pacajá – Pará - SILVA, Elisvaldo Rocha (2021)
The use of machines in various operations of preparation, sowing, crop treatment, harvesting and grazing of cattle and others, has been pointed as the main cause of compaction in Brazilian soils. As a result it reduces root growth and development, increases soil erosion through less water in-filtration. Therefore, the objective was to evaluate the physical and chemical parameters of soil: density, particle size, P, K, Ca, Mg, Al, CTC, Ph, organic matter (MO), base sum (SB), saturation by base (V%) and aluminum saturation (m%). The study was conducted on a 40-hectare rural property in the vicinal Portel, Pacajá-PA, the period of soil samples was collected in February and October 2018, with rainy and dry periods respectively. Undisturbed samples for physical analysis and deformed samples for chemical analysis were collected in the soil layers (0-20 and 20-40 cm). The experimental design was completely randomized (IHD), being the treatments: Secondary Ve-getation, Pasture and Mechanized Area, applying the Wilcoxon t test (P <0.05) significance. Through the density analysis it was found that the pasture area presented greater compaction in both harvest periods and all treatments presented low fertility conditions, especially the mechani-zed area, whose incorporation of organic matter in the soil. by harrowing possibly contributed to such fertility.